Reading Ability Profile of Fifth Grade Elementary School Students: A Comprehensive Analysis Using the Early Grade Reading Assessment (EGRA) - Jaka Nurhidayat; Yunus Abidin (Universitas Negeri Malang, 2025)
Abstract: Reading ability is crucial to academic achievement, yet identifying students’ abilities solely based on communication without accurate data can hinder effective learning-strategy interventions. This study aims to identify students’ reading profiles, including letter recognition, syllables, words, listening, reading fluency, and comprehension, using a quantitative, descriptive approach with 36 fifth-grade students as samples. The main instrument is the Early Grade Reading Assessment (EGRA). Results show students possess strong decoding skills, with perfect mastery of letters, syllables, words, and excellent reading fluency (K1, K2). This confirms the achievement of automaticity standards in decoding. However, listening comprehension remains a challenge for a quarter of students, while in reading comprehension, 47.2 percent of students scored below perfect on P1, and most scored low on P2. This shows that reading ability does not always align with students’ comprehension skills. The Understanding Factor (C) is a significant cognitive barrier, manifested in the failure of inference and information synthesis. These findings validate the Simple View of Reading model and emphasize the importance of shifting the intervention paradigm from a focus on decoding to the explicit and systematic development of comprehension strategies.Abstrak: Kemampuan membaca sangat penting bagi prestasi akademik siswa, namun mengidentifikasi kemampuan siswa hanya berdasarkan komunikasi tanpa data yang akurat dapat menghambat intervensi strategi belajar yang efektif. Studi ini bertujuan untuk mengidentifikasi profil kemampuan membaca siswa, termasuk pengenalan huruf, suku kata, kata, mendengarkan, kelancaran membaca, dan pemahaman, menggunakan pendekatan kuantitatif deskriptif dengan 36 siswa kelas lima sebagai sampel. Instrumen utama yang digunakan adalah Early Grade Reading Assessment (EGRA). Hasil menunjukkan bahwa siswa memiliki keterampilan decoding yang kuat, dengan penguasaan sempurna terhadap huruf, suku kata, kata, dan kelancaran membaca yang excellent (K1, K2). Hal ini mengonfirmasi pencapaian standar otomatisasi dalam decoding. Namun, pemahaman mendengarkan tetap menjadi tantangan bagi seperempat siswa, sementara pada pemahaman membaca, 47,2 persen siswa memperoleh skor di bawah sempurna pada P1, dan sebagian besar memperoleh skor rendah pada P2. Hal ini menunjukkan bahwa kemampuan membaca tidak selalu sejalan dengan keterampilan pemahaman siswa. Faktor Pemahaman (C) merupakan hambatan kognitif yang signifikan, yang tercermin dalam kegagalan dalam membuat kesimpulan dan sintesis informasi. Temuan ini mengonfirmasi model Simple View of Reading dan menekankan pentingnya mengubah paradigma intervensi dari fokus pada dekodasi menjadi pengembangan eksplisit dan sistematis strategi pemahaman.